2021
DOI: 10.4236/jbbs.2021.119017
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Metagenomic Next-Generation Sequencing in <i>Angiostrongylus cantonensis</i> Encephalitis/Meningitis

Abstract: Objective: Angiostrongylus cantonensis (A. cantonensis) is an important parasite, which causes neurological infection in children, and is generally difficult to diagnose. We analyzed the significance of metagenomic next-generation sequencing in diagnosing A. cantonensis encephalitis/meningitis in children to provide a reference for clinical diagnosis. Methods: The case collection of A. cantonensis encephalitis/meningitis was from July 2018 to August 2020.The patients' clinical characteristics and pathogen were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In clinical practice, the delayed diagnosis of Angiostrongylus eosinophilic meningitis due to its atypical symptoms is an important problem in many hospitals because it can cause fatal outcomes. Despite the recent introduction of a powerful and sensitive molecular diagnostic tool (metagenomic next-generation sequencing) for the specific identification of Angiostrongylus cantonensis DNA sequences in clinical specimens [ 28 , 29 ], the diagnosis of active/acute neuroangiostrongyliasis remains a challenge in resource-limited settings because of high operating costs and the requirement for laboratory infrastructure [ 29 ]. Other rapid and cost-effective assays for the point-of-need diagnosis are still required to meet the demand of appropriate tests for use in resource-poor settings or remote endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the delayed diagnosis of Angiostrongylus eosinophilic meningitis due to its atypical symptoms is an important problem in many hospitals because it can cause fatal outcomes. Despite the recent introduction of a powerful and sensitive molecular diagnostic tool (metagenomic next-generation sequencing) for the specific identification of Angiostrongylus cantonensis DNA sequences in clinical specimens [ 28 , 29 ], the diagnosis of active/acute neuroangiostrongyliasis remains a challenge in resource-limited settings because of high operating costs and the requirement for laboratory infrastructure [ 29 ]. Other rapid and cost-effective assays for the point-of-need diagnosis are still required to meet the demand of appropriate tests for use in resource-poor settings or remote endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in technology have made it an invaluable diagnostic tool for clinicians. mNGS is particularly useful for detecting infectious agents in cases of encephalitis and meningitis [ 25 , 26 ]. As an example, some studies have demonstrated the potential of mNGS in the diagnosis of meningitis and encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, some studies have demonstrated the potential of mNGS in the diagnosis of meningitis and encephalitis. Fan et al have demonstrated that by utilizing mNGS, infectious diseases caused by pathogens that are less frequently encountered, such as Angiostrongylus cantonensis , can be accurately diagnosed, which in turn results in improved patient outcomes and care [ 26 ]. Wilson et al also demonstrated the comprehensive spectrum of potential causes that can be identified by a single mNGS assay, including viral, bacterial, fungal, and parasitic pathogens, showcasing its utility in diagnosing complex central nervous system infections [ 25 ].…”
Section: Introductionmentioning
confidence: 99%